ALK‐positive primary cutaneous anaplastic large cell lymphoma: a case report and review of the literature. (23rd October 2017) - Geller, Shamir; Canavan, Theresa N.; Pulitzer, Melissa; Moskowitz, Alison J.; Myskowski, Patricia L.
Abstract: Anaplastic large cell lymphoma (ALCL) limited to the skin is a distinct disease that is designated primary cutaneous ALCL (pcALCL). It has an indolent course with a significantly better prognosis compared to systemic ALCL (sALCL). Anaplastic lymphoma kinase (ALK) expression in lesions of cutaneous ALCL is classically considered to be a marker for skin involvement by sALCL. However, recent reports of patients with ALK‐positive pcALCL challenge this concept and raise prognostic and therapeutic dilemmas. Herein, we report a case of ALK‐positive pcALCL in a 45‐year‐old woman who was treated with local radiotherapy. We review previously reported cases in the literature to better characterize this rare variant. Overall, the rates of cutaneous recurrence, systemic dissemination, and disease‐related mortality in ALK‐positive pcALCL do not differ from those previously reported in pcALCL. ALK‐positive pcALCL is diagnosed at younger age and has a better disease course in children compared to adults with lower incidences of skin recurrence and progression to systemic disease. We conclude that ALK‐positivity in cutaneous ALCL does not necessarily imply systemic disease. ALK‐positive pcALCL has an excellent prognosis and should be treated by excision and/or radiotherapy. However, patients must remain under close long‐term follow‐up as recurrence and progression to systemic disease may occur.